Author Correction: Effect of induced hypoglycemia on inflammation and oxidative stress in type 2 diabetes and control subjects - Hassan Kahal (9999461) (2020)
Correction to: Effect of induced hypoglycemia on inflammation and oxidative stress in type 2 diabetes and control subjects. http://dx.doi.org/10.1038/s41598-020-61531-z, published online 16 March 2020. The original version of this Article contained a typographical error in the spelling of the author Johannes Graumann, which was incorrectly given as Johannes Grauman. This has now been corrected in the PDF and HTML versions of the Article, and in the accompanying Supplementary Information file. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-020-66189-1